Epidemiology of maxillofacial injuries in “Heratsi” No 1 university hospital in Yerevan, Armenia: a retrospective study - Lusine V. Aleksanyan; Anna Yu Poghosyan; Martin S. Misakyan; Armen M. Minasyan; Aren Yu Bablumyan; Artashes E. Tadevosyan; Armen A. Muradyan (BMC Oral Health, 2022)
Abstract Background The aim of this study was to perform a retrospective analysis of the prevalence, etiologies, types of maxillofacial injuries (MFIs), sites of maxillofacial fractures (MFFs) and their management in Yerevan, Armenia. Methods A retrospective cross-sectional study was conducted. The extracted data included age, sex, date of referral, mode of injury, etiology, radiology records and treatment methods. Study outcomes were measured using percentages, means, standard deviations and tests of proportions. P < .05 was considered significant. Results A total of 204 patients had a mean age of 36.26 ± 1.08 years (156 males and 48 females), and a total of 259 MFIs were recorded between 2017 and 2020. Interpersonal violence was found to be the most common etiology of MFFs in this study (42.1%), followed by road traffic accidents (RTAs) (27.9%) and falls (18.6%). The nasal bone was the most common injury site (47.5%), followed by the mandible (31.4%) and zygomatic complex (11.7%). The most common fracture site was the mandibular angle (37.9%), followed by the symphysis/parasymphysis (28.1%) and body (12.6%). Isolated soft tissue injuries were reported in 5.9% of the cases. The majority of MFFs were treated by open reduction and internal fixation. Conclusion Interpersonal violence, followed by RTAs and falls, was the most common cause of MFIs. Males in the 21–30 years age group had the highest MFI incidence rate. The nasal bone was the most common injury site, followed by the mandible and zygomatic complex. Social education with the objective of reducing aggression and interpersonal conflict should be improved, and appropriate RTA prevention strategies should be strengthened and implemented.